A crítica pós-moderna: analítica da interação e da sociabilidade - Carlos A. Gadea (Universidade do Vale do Rio dos Sinos (UNISINOS), 2007)
As one attempts to approach the multiple dimensions of modernity and its nexus with contemporary theoretical debates, one should not omit the different contributions made by the so-called post-modern critique. This article discusses these contributions on the basis of those theoretical elements that are presented as heirs of a neglected sociological tradition in the academia because of the occasional hegemony of analytical perspectives that are more rooted in structural determinism. When the post-modern critique reformulates issues of sociability and political and cultural behavior and resorts to an analytical framework in which concepts such as plurality, multiplicity, fragmentation and relativism gain importance, it is doing nothing else than reintroducing a theoretical legacy and a sociological adventure that arise, for instance, from the sociological impressionism of Simmel, the pragmatism of William James and psychosocial studies of Georg H. Mead. The article claims that the post-modern critique is in a way defined as a kind of reuse of theoretical approaches to social interaction ranging from philosophical pragmatism and eclecticism to etnomethodology and the so-called cultural studies